The effect of financial technology, innovation, business strategy, and market orientation on business performance among Indonesian SMEs: a study in Riau province - Enni Savitri,; Nik Herda Nik Abdullah,; Andreas,; Volta Diyanto,; Almasdi Syahza, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The pandemic's negative impact on SMEs’ performance have been particularly felt as a result of changes in consumer behavior. Therefore, strategic actions are required to accelerate the growth of SMEs in the postpandemic era. Based on the Dynamic Capabilities Theory, the aim of this study was to analyze the effect of financial technology, innovation, business strategy, and market orientation on the business performance of SMEs in Riau Province, Indonesia. Using purposive sampling, survey data was collected from a sample of 123 SME owner-managers. Data analysis using partial least squares structural equation modeling showed that financial technology, innovation, business strategy, and market orientation significantly affect the business performance of SMEs. SME owner-managers use financial technology to make new breakthroughs through innovation, implement more diverse business strategies, and improve market orientation. The findings suggest that long-term digital technology development strategies are required as a platform for SMEs to grow.